Socialization of Technology Utilization and Tax Modernization at SMK N 1 Medan - Yunita Sari Rioni; Tia Novira Sucipto; Oktarini Khamilah Siregar; Anwar Suhut (International Forum of Researchers and Lecturers, 2022)
The community service activity with the title